A case of tertiary syphilis manifested with multiple skin gummas - T. V. Krasnoselskikh (Vestnik Dermatologii i Venerologii, 2017)
The tertiary cutaneous syphilis has become extremely rare as a result of the effective treatment of early syphilis with penicillin and occasional antibiotic therapy for concomitant infections. We report a case of tertiary gummatous syphilis associated with asymptomatic neurosyphilis that was initially misdiagnosed as basal cell carcinoma of the skin. A 67-year-old woman presented with the 18-month history of multiple, firm, bluish-red asymptomatic nodes on the parietal scalp, chin and lateral part of the trunk that had developed without preceding trauma. One node on the trunk had small central ulceration covered with dry yellowish crust. On the left retroauricular area the brownish-purple atrophic scar was observed. Blood tests revealed reactive VDRL, ELISA and TPHA assays. Skin biopsy has showed endarteritis with endothelial swelling and caseating granulomas along with plasmocytic infiltrate in the dermis and subcutaneous tissue. Increased lymphocyte count and the positive VDRL test with cerebrospinal fluid have confirmed the diagnosis of asymptomatic syphilitic meningitis in this patient. The treatment with aqueous penicillin intravenously has lead to resolution of the skin infiltrates and progressive more than 4-fold reduction of follow-up serum VDRL titers. This case is reported as a reminder of the possibility of tertiary syphilis with misleading clinical patterns in patients infected during the epidemics of 1995-2000. We would like to emphasize the necessity to perform timely serological and pathomorphological study to prevent misdiagnosis and mistreatment.